Effects of the Tanaka Line on the genetic structure of Bombax ceiba (Malvaceae) in dry‐hot valley areas of southwest China. Issue 7 (1st March 2018) - Ju, Miao‐Miao; Fu, Yi; Zhao, Gui‐Fang; He, Cheng‐Zhong; Li, Zhong‐Hu; Tian, Bin
Abstract: Southwest China is an important biodiversity hotspot. The interactions among the complex topography, climate change, and ecological factors in the dry‐hot valley areas in southwest China may have profoundly affected the genetic structure of plant species in this region. In this study, we determined the effects of the Tanaka Line on genetic variation in the wild Bombax ceiba tree in southwest China. We sampled 224 individuals from 17 populations throughout the dry‐hot valley regions. Six polymorphic expressed sequence tag–simple sequence repeat primers were employed to sequence the PCR products using the first‐generation Sanger technique. The analysis based on population genetics suggested that B. ceiba exhibited a high level of gene diversity ( H E : 0.2377–0.4775; I : 0.3997–0.7848). The 17 populations were divided into two groups by cluster analysis, which corresponded to geographic characters on each side of the Tanaka Line. In addition, a Mantel test indicated that the phylogeographic structure among the populations could be fitted to the isolation‐by‐distance model ( r 2  = .2553, p  < .001). A barrier test indicated that there were obstacles among populations and between the two groups due to complex terrain isolation and geographic heterogeneity. We inferred that the Tanaka Line might have promoted the intraspecific phylogeographic subdivision and divergence of B. ceiba . These results provide new insights into the effects of the Tanaka Line on genetic isolation and population differentiation of plant species in southwest China. Abstract : In the study, we used six pairs of EST‐SSR primers to explore population structure and diversity of B .  cieba wild populations from both sides of Tanaka Line. Moreover, we used the Sanger sequencing of PCR products to make the results more accurate and reliable.